Perilaku Menyimpang Baku Piara di Kota Manado - Kalangi, Yani Semuel Zeth; Karebungu, Ferdinan Karebungu; Tasik, Femmy (JURNAL ILMIAH SOCIETY, 2018)
This research was conducted to reveal about the causes of the community doing misbehavior of the pets, when they know that such deviant behavior is a violation of norms, rules and values. It will also examine the causes of living community members who can not carry out marriage. The purpose of this research is to describe, analyze and interpret the cause of the community members of Tongkaina Sub-District of Bunaken Sub-district of Manado City who live in pets can not carry out legitimate marriage and to describe, analyze and interpret the cause of community members of Tongkaina Urban Village Bunaken Manado City behave deviantly. Research method used in this research is research method in qualitative approach with data collecting technique that is participant observation technique, deep in interview and documentation. This research focuses on the community members who live standard in Tongkaina Village Bunaken Subdistrict Manado City which is divided into three, namely: Members of the community who live pajamas have been married, members of the community who live standard never married as well as public figures and religious leaders. The cause of living community members can not perform legitimate marriages: The reasons for the administration of the marriage requirements have not met the legal requirements of marriage, namely the lack of marriage material support in the form of important papers such as the Divorce Act. The cause of deviant behavior in the Village Tongkaina Sub District Bunaken Manado City is: because of the dysfunction in the family of family inability to carry out their duties / functions or failing functions such as husband not working, husbands love to beat / not protect wife. In addition there is a third party, namely the existence of the intervention of others. Like a parent, a pair of pets.Keywords : Participation, marriage, councelling